Polysubstance-induced relapse of schizoaffective disorder refractory to high-dose antipsychotic medications: a case report. (December 2016) - Tucker, Murray; Kekulawala, Sebastian; Kent, Michelle; Mostafa, Sam; Harvey, Richard
Abstract Background The high prevalence of comorbid illicit drug use in persons with chronic psychotic illness represents a strong determinant of psychotic relapse and rehospitalization. Epidemiological studies indicate changing patterns of illicit drug use in Australia, which are concerning because of increased use of crystal methamphetamine, also known as "ice." An important complication of habitual use of crystal methamphetamine is the development of a dose-dependent acute psychotic reaction. We report a case of an acute psychotic relapse in response to polydrug use most notable for multiple recent binges of crystal methamphetamine. Unlike previously described case reports, our patient's acute psychosis was refractory to ultra-high doses of multiple antipsychotic medications. This presented safety challenges due to the risk of serious side effects with high-dose antipsychotic medications. Case presentation A 30-year-old white man with a past history of schizoaffective disorder was brought to our emergency department by the police in a state of extreme agitation, combativeness, and paranoia after use of cannabis and crystal methamphetamine. Despite existing compliance with zuclopenthixol decanoate depot medication, he required multiple emergency injections of zuclopenthixol acetate, and regular high-dose droperidol, chlorpromazine, and lorazepam. However, he remained severely agitated and psychotic with continuous threats of harm to others. A test of antipsychotic drug metabolism by cytochrome P450 enzymes did not reveal a pharmacogenetic cause for the poor therapeutic efficacy of antipsychotic medications. His psychosis did not appear to be modified by psychoactive medications but was instead self-limited to the presence of endogenous methamphetamine within his system. He fully recovered 96 to 120 hours post-presentation and was discharged home with out-patient clinic follow-up. Conclusions The current case highlights the challenging nature of a severe psychotic relapse precipitated by illicit substances that is resistant to medical management. High doses of multiple antipsychotic medications may be required to manage dangerous behaviors associated with these acute psychotic relapses. These patients require close monitoring for adverse effects with adjustment of dosing to ensure the optimal balance of risk versus benefit while the patient is acutely psychotic. The results are of relevance for the management of psychiatric emergencies in emergency departments and acute mental health settings.